2009
DOI: 10.1128/ecosalplus.3.6.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Menaquinone (Vitamin K 2 ) and Ubiquinone (Coenzyme Q)

Abstract: Escherichia coli and Salmonella contain the naphthoquinones menaquinone (MK; vitamin K 2 ) and demethylmenaquinone and the benzoquinone ubiquinone (coenzyme Q; Q). Both quinones are derived from the shikimate pathway, which has been called a "metabolic tree with many branches." There are two different pathways for the biosynthesis of the naphthoquinones. The vast majority of prokaryotes, including E. coli and Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 174 publications
(227 reference statements)
1
70
0
Order By: Relevance
“…For example, 1 g taurine per kg DM is required in kibbled diets whereas canned diets require 2 g taurine per kg DM diet50. Additionally, the relationship between taurine and Maillard reaction products and intestinal microbiota has been of interest for the cat since work published in 1996 showed that Maillard reaction products induced taurine depletion in the cat and that this could be reversed with antibiotics65.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 1 g taurine per kg DM is required in kibbled diets whereas canned diets require 2 g taurine per kg DM diet50. Additionally, the relationship between taurine and Maillard reaction products and intestinal microbiota has been of interest for the cat since work published in 1996 showed that Maillard reaction products induced taurine depletion in the cat and that this could be reversed with antibiotics65.…”
Section: Resultsmentioning
confidence: 99%
“…Members of this enzyme group are involved in the biosynthesis of both primary metabolites such as ubiquinones and menaquinones (Boronat and Rodriguez-Concepcion 2015;Meganathan and Kwon 2009) and secondary metabolites like microbial and plant natural products (Holm et al 2014;Wang et al 2014;Yazaki et al 2009;Zeyhle et al 2014a, b).…”
Section: Membrane-bound Prenyltransferases For Aromatic Substratesmentioning
confidence: 98%
“…This pathway consists of at least nine enzymes that catalyze the formation of menaquinone from chorismate [12, 13, 16] . The fifth enzyme, MenE, is an acyl-CoA ligase which ligates CoA to OSB via an OSB-AMP intermediate.…”
Section: Figurementioning
confidence: 99%